The Effect of Risk Factors on Stunting Events the Titi Papan Puskesmas, Mabar Hilir Kelurahan, Medan Deli District Medan City, 2021 - Susanti br Perangin-Angin (Eduvest - Journal of Universal Studies, 2022)
The World Health Organization (WHO) collected stunting data showing that Indonesia is one of the three countries with the highest prevalence in the South-East Asia Region (SEAR). Health problems that affect infants are stunting or short stature due to chronic malnutrition where malnutrition is a global problem, including in Indonesia. This research is an analytic observational study with a case control study. The design was carried out at the Titi Papan Health Center, Mabar Hilir District, Medan Deli Regency in 2021 to analyze the influence of risk factors on stunting events with a sample of 88 children under five, 44 cases and 44 controls, sampling was carried out purposively where cases and controls were taken in one population. Data were obtained from Puskesmas, Medan City Health Office, observations, direct interviews with respondents using questionnaires. The results of the study concluded that the most influential variable on the incidence of stunting was family income (p = 0.000, Exp(B) = 9.208). Factors that significantly influence the incidence of stunting are birth weight (p = 0.001, OR = 2.375), education (p = 0.001, OR = 6.923), family income (p = 0.000, OR = 15.857), availability of clean water facilities . (p = 0.000, OR = 9.643), family latrine facilities (p = 0.001, OR = 2.333), sewerage ownership (p = 0.000), OR = 0.405. The need for intensive counseling by health workers regarding factors related to stunting, to increase public awareness to change bad habits that are contrary to health and can cause stunting in toddlers.